An Attenuated Zika Virus Encoding Non-Glycosylated Envelope (E) and Non-Structural Protein 1 (NS1) Confers Complete Protection against Lethal Challenge in a Mouse Model - Annamalai, Arun S. (Vaccines (Basel), 2019)
Zika virus (ZIKV), a mosquito-transmitted flavivirus, emerged in the last decade causing serious human diseases, including congenital microcephaly in newborns and Guillain-Barré syndrome in adults. Although many vaccine platforms are at various stages of development, no licensed vaccines are currently available. Previously, we described a mutant MR766 ZIKV (m2MR) bearing an E protein mutation (N154A) that prevented its glycosylation, resulting in attenuation and defective neuroinvasion. To further attenuate m2MR for its potential use as a live viral vaccine, we incorporated additional mutations into m2MR by substituting the asparagine residues in the glycosylation sites (N130 and N207) of NS1 with alanine residues. Examination of pathogenic properties revealed that the virus (m5MR) carrying mutations in E (N154A) and NS1 (N130A and N207A) was fully attenuated with no disease signs in infected mice, inducing high levels of humoral and cell-mediated immune responses, and protecting mice from subsequent lethal virus challenge. Furthermore, passive transfer of sera from m5MR-infected mice into naïve animals resulted in complete protection from lethal challenge. The immune sera from m5MR-infected animals neutralized both African and Asian lineage viruses equally well, suggesting that m5MR virus could be developed as a potentially broad live virus vaccine candidate.